2022
DOI: 10.48550/arxiv.2210.02441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ask Me Anything: A simple strategy for prompting language models

Abstract: Large language models (LLMs) transfer well to new tasks out-of-the-box simply given a natural language prompt that demonstrates how to perform the task and no additional training. Prompting is a brittle process wherein small modifications to the prompt can cause large variations in the model predictions, and therefore significant effort is dedicated towards designing a painstakingly perfect prompt for a task. To mitigate the high degree of effort involved in prompting, we instead ask whether collecting multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Crowdworkers have different viewpoints [6,24,83] and sourcing perspectives from expert crowdworkers [27] or from workers with various skill levels [102] can extend this variety. For LLMs, leveraging their stochastic nature (e.g., with a higher temperature parameter setting) or using different models or prompt variants (including role-based prompts) can source a variety of responses [12,117,143]. In some cases one can automatically calculate the optimal mix of LLMs for a task [100].…”
Section: Response Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Crowdworkers have different viewpoints [6,24,83] and sourcing perspectives from expert crowdworkers [27] or from workers with various skill levels [102] can extend this variety. For LLMs, leveraging their stochastic nature (e.g., with a higher temperature parameter setting) or using different models or prompt variants (including role-based prompts) can source a variety of responses [12,117,143]. In some cases one can automatically calculate the optimal mix of LLMs for a task [100].…”
Section: Response Diversitymentioning
confidence: 99%
“…Simplifying tasks can increase quality [28,83,120,142]. Another strategy is to adapt the subtask to fit the worker's capabilities [12,23,109,120]. For example, researchers found that crowdworkers were better at generating predictive features than at estimating if a feature is predictive; so they adapted the workflow accordingly [25].…”
Section: Response Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…into the importance of prompt engineering, the development of frameworks and strategies for structuring prompts, and the evaluation of LLM performance on complex tasks. 5,6,[24][25][26][27][28][29] These studies highlight the significance of prompt engineering when working with models like GPT-4 and provide relevant context for using LLMs in advanced research, such as the present study on SRT. This work differs from these studies in that it specifically evaluates GPT-4, which is posited to possess emergent, foundational AGI behaviors.…”
Section: Related Workmentioning
confidence: 92%
“…SuperGLUE: We evaluate models on the SuperGLUE (Wang et al, 2019) with the parsing pipeline of (Arora et al, 2022). For all tasks except WIC, CB and BoolQ, we generate a response using greedy decoding, then check for the gold label.…”
Section: A3 Downstream Evaluationmentioning
confidence: 99%